Submerged vascular anastomosis. A technique for vascular suturing in experimental microsurgery - Balduino Ferreira de Menezes Neto; Fausto Viterbo de Oliveira Neto; Murilo Sgarbi Secanho; Laísa Brandão Carvalho; Weber Ribolli Moragas; Matheus Scuracchio Fernandes (Acta Cirúrgica Brasileira, 2021)
ABSTRACT Purpose: To evaluate the impact of submersion of the microsurgical anastomosis suture area using saline (0.9% NaCl) in an experimental laboratory during the training of medical students and resident physicians. Methods: Wistar rats (n = 10) were selected to have the two femoral arteries sectioned and anastomosed end-to-end under optical magnification. They were randomly divided, so that on one side suturing was performed under submersion with saline, and the contralateral side was kept dry during the procedure. The surgical times, as well as the patency within 30 min and 72 h of the procedure, were evaluated. Results: Six male Wistar rats survived the surgical anesthetic procedure, with the average initial weight of 243.3 g and the average artery diameter of 0.86 mm, with average time of 15.67 min for the submerged technique and 20.50 min for the dry technique (p = 0.03). The failure rates were 17 and 50% for the submerged group and the dry one, respectively (p = 0.62). Conclusions: Submerged microvascular suture does not compromise the patency of the vessel or increase the time of anastomosis. Therefore, it is a strategy that can be applied by the surgeon according to his/her technical preferences.